Natural compounds as inhibitors of SARS-CoV-2 endocytosis: A promising approach against COVID-19 - Kiani, Aysha Karim; Dhuli, Kristjana; Anpilogov, Kyrylo; Bressan, Simone; Dautaj, Astrit; Dundar, Munis; Beccari, Tommaso; Ergoren, Mahmut C.; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: The recent COVID-19 pandemic caused by SARS-CoV-2 affected more than six million people and caused thousands of deaths. The lack of effective drugs or vaccines against SARS-CoV-2 further worsened the situation. This review is focused on the identification of molecules that may inhibit viral entry into host cells by endocytosis. Methods: We performed the literature search for these natural compounds in the articles indexed in PubMed. Results: Natural products against viral infections have been gaining importance in recent years. Specific natural compounds like phytosterols, polyphenols, flavonoids, citrus, galangal, curcuma and hydroxytyrosol are being analyzed to understand whether they could inhibit SARS-CoV-2. Conclusions: We reviewed natural compounds with potential antiviral activity against SARS-CoV-2 that could be used as a treatment for COVID-19.